2014
DOI: 10.1186/s13012-014-0186-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving community case management of diarrhoea and pneumonia in district Badin, Pakistan through a cluster randomised study—the NIGRAAN trial protocol

Abstract: BackgroundDiarrhoea and pneumonia contribute 30% of deaths in children under 5 in Pakistan. Pakistan’s Lady Health Workers Programme (LHW-P) covers about 60% of the population but has had little impact in reducing morbidity and mortality related to these major childhood killers. An external evaluation of the LHW-P suggests that lack of supportive supervision of LHWs by lady health supervisors (LHSs) is a key determinant of this problem. Project NIGRAAN aims to improve knowledge and skills of LHWs and community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 15 publications
(11 reference statements)
0
31
0
Order By: Relevance
“…Nigraan (named for an Urdu word meaning supervisor), a cluster randomised controlled trial, was conducted in Badin district in Pakistan . Badin is predominantly rural, spans 6726 km 2 and has a population of 1.35 million.…”
Section: Methodsmentioning
confidence: 99%
“…Nigraan (named for an Urdu word meaning supervisor), a cluster randomised controlled trial, was conducted in Badin district in Pakistan . Badin is predominantly rural, spans 6726 km 2 and has a population of 1.35 million.…”
Section: Methodsmentioning
confidence: 99%
“…A notable strength of this is study is that despite the long timespan of this analysis (1989-2014), about a third of the study staff were involved in both the initial study and more recent follow-up and were able to collect comparable information during both periods. However, the supervision and support given to the study staff was more comprehensive in Study 1, which likely had a positive impact on health worker performance as suggested by other studies [40,46]. Similarly, in Study 1 community members could more easily meet with a member of the study team if their child became sick in between visits, but in Study 2…”
Section: Discussionmentioning
confidence: 90%
“…The main study outcome was improvement of CCM for childhood diarrhea and pneumonia. Further details of the study are published elsewhere [17].…”
Section: Nigraan Intervention and Study Participantsmentioning
confidence: 99%
“…Independent studies including external evaluations of the program shed some light on the factors responsible for this poor outcome. These are poor clinical mentorship and supervisory skills of Lady Health Supervisors (LHS) and dysfunctional supervisory links between LHSs and LHWs [11,[13][14][15][16][17][18]. In order to bridge these supervisory gaps, the Aga Khan University Pakistan in collaboration with health department, government of Sindh introduced an IR project called NIGRAAN.…”
Section: Introductionmentioning
confidence: 99%